Leroy L. Cogger: A Pioneer in Optical Observations From Space - Andrew W. Yau; Andrew D. Howarth; David J. Knudsen; J. Sandy Murphree; Trond S. Trondsen (Perspectives of Earth and Space Scientists)
Abstract This perspective is in memory of Leroy Leonard Cogger, a pioneer in optical imaging of the aurora and the airglow, who passed away in October 2022 in Canada at the age of 85. In his 40‐plus‐year career, which spans both space and ground‐based optical instrumentation and observations, Dr. Cogger has made significant contributions to the development of instruments for several space missions and ground observatories, including the world's first truly digital (charge‐coupled device) camera to be used in the field, the UV auroral imagers for the Swedish Viking and Freja satellites, the NASA IMAGE satellite, and the Russian INTERBALL‐2 satellite, respectively, and the fast near‐infrared auroral imager on the Canadian CASSIOPE/Enhanced Polar Outflow Probe satellite. He has also collaborated and mentored the next generation of space scientists in Canada and Europe in many areas of auroral and airglow research; he was particularly adept at combining diverse observations to provide insight into a wide array of atmospheric phenomena. His legacies go well beyond his contributions in the peer‐reviewed literature and innovative instrumentation: his scientific vision and leadership played an indispensable role in the Canadian space science research agenda, and his commitment to mentoring has left an indelible mark on many of his students and associates. He exemplified AGU's motto of “Unselfish cooperation in research.” His gentle and quiet spirit, his passion for research and in making a difference in life will be very much missed by his many friends and colleagues in Canada and abroad alike, as will his great sense of humor.